2018
DOI: 10.1002/2018gl077076
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Influence of DE3 Tide on the Occurrence of Equatorial Counterelectrojet

Abstract: The long‐term Challenging Minisatellite Payload magnetometer data are analyzed to derive the equatorial counterelectrojet (CEJ) signatures globally over a range of local times. The resultant local time‐longitude map of CEJ occurrence rate shows a strong influence of the diurnal eastward propagating wave number 3 (DE3) nonmigrating tide during July–September months. DE3 is also shown to account for the reduction of CEJ occurrence at certain longitudes. These aspects of DE3 tide‐CEJ relationship have implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
(60 reference statements)
5
18
0
Order By: Relevance
“…The EEJ intensity sharply decreases from 90°W to 40°W, and the global analysis of Swarm data suggest that this longitudinal gradient is partly due to the wave‐4 longitudinal structure arising from nonmigrating tides and stationary planetary waves. The wave‐4 effect is found not only in ACEJ, as recently reported by Singh et al (), but also in MCEJ. TIEGCM results suggest that the longitudinal variation of the EEJ intensity resulting from migrating tides also makes a contribution to the observed longitudinal gradient of the EEJ intensity over the American sector. Both the effects of migrating tides (across the longitudinally varying geomagnetic main field) and wave‐4 pattern are of similar size and, combined, lead to a stronger EEJ in the Peruvian sector than in the Brazilian sector during the northern‐hemisphere summer, resulting in higher CEJ occurrence rates in the Brazilian sector.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The EEJ intensity sharply decreases from 90°W to 40°W, and the global analysis of Swarm data suggest that this longitudinal gradient is partly due to the wave‐4 longitudinal structure arising from nonmigrating tides and stationary planetary waves. The wave‐4 effect is found not only in ACEJ, as recently reported by Singh et al (), but also in MCEJ. TIEGCM results suggest that the longitudinal variation of the EEJ intensity resulting from migrating tides also makes a contribution to the observed longitudinal gradient of the EEJ intensity over the American sector. Both the effects of migrating tides (across the longitudinally varying geomagnetic main field) and wave‐4 pattern are of similar size and, combined, lead to a stronger EEJ in the Peruvian sector than in the Brazilian sector during the northern‐hemisphere summer, resulting in higher CEJ occurrence rates in the Brazilian sector.…”
Section: Discussionsupporting
confidence: 81%
“…Singh et al () showed that the DE3 tide gives rise to the wave‐4 longitudinal pattern in the occurrence rate of ACEJ. Our results suggest that the wave‐4 longitudinal pattern is also an important source of longitudinal variability for the MCEJ occurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability demonstrated at 5° separations in our study is direct evidence of the influence of short scale length processes. The other significant finding from our study is for the westward increase in CEJ amplitude and occurrence that have been attributed to wave‐tide interaction. We have shown that the same trend is evident for both quiet and disturbed periods indicating the pervasive influence of DE3 tide corroborated by Bulusu et al () and Singh et al ().…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes, the direction of the current reverses to westward, a phenomenon called counter electrojet (CEJ) due to a number of physical mechanisms including (but not limited to) ionospheric variability during stratospheric warming periods (Siddiqui et al, ; Stening et al, ; Vineeth et al, ), westward prompt penetrating electric field leading to ionospheric disturbed dynamo (Kikuchi et al, ; Yizengaw et al, ), and vertical upward winds uplifting ions thereby cancelling the vertical polarization electric field (Raghavarao & Anandarao, ). Therefore, the complex variability of CEJ is influenced/modulated by variations in local time, longitude (mainly related to migrating and nonmigrating tides), seasonal dependence, lunar cycles, magnetic activity, and solar activity (Marriott et al, ; Mayaud, ; Rabiu et al, ; Rastogi, ; Singh et al, ; Soares et al, ; Zhou et al, ). Since the CEJ's first detection (Gouin, ), various studies have investigated the CEJ occurrence based mainly on magnetometers deployed in equatorial and/or low‐latitude regions (e.g., Alex & Mukherjee, ; Rastogi, , and references therein).…”
Section: Introductionmentioning
confidence: 99%